Avaliação do reaproveitamento de areia de fundição como agregado em misturas asfálticas densas - COUTINHO NETO, Benedito (2004)
Foundry sand is an industrial solid waste resulting from sand casting process in foundry industries. Depending on the type of foundry process (green sand molding, shell sand molding, molding using synthetic resin and others) and of the type cast metal, this waste may contain elements and/or chemical compounds that may cause environmental impact. The substances that may be found in foundry sand proceed partly from the type of the metal and partly from the agglutinant used on the process. The purpose of this research is to present an alternative study for the use of the foundry sand, reusing it in the composition of the aggregate for asphalt concrete and thus to contribute to minimize the environmental impact caused for this waste. To reach this purpose, classification tests of solid wastes were run in virgin sand and foundry sand and asphaltic mixtures not compacted containing both types of sand. This investigation considered the possibility of this waste when incorporated to asphaltic mixture to pollute the environment. Leaching with soxhlet extractor test in specimen of asphaltic mixture with 15% of foundry sand was also realized to evaluate the performance of this material a long-term period in environmental terms. In order to verify the performance in paving, the mixtures were submitted to Marshall method of mix design and to the tests of resilient modulus, indirect tensile strength, cantabro, resistance of compacted bituminous mixture to moisture-induced damage and static creep. Based on the results, it could be concluded that, in a general way, the reuse of foundry sand in asphaltic paving is viable, once the asphaltic mixtures containing this residue presented good mechanical properties. Besides the classification tests of solid wastes realized in asphaltic mixture containing foundry sand, which original classification as class II - no inert, passed to a classification of asphaltic mixture class III - inerte, what suggests that the waste was encapsulated in hot mix asphalt.